Targeted Digital Outreach-Based Socialization: A Strategy to Enhance Students' Understanding of the Study Program's Academic Vision - Alghadari, Fiki; Pasaribu, Feri Tiona; Fitriani, Silvia (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
Promoting lifelong learning opportunities for all was part of the Sustainable Development Goal 4 program. However, transitioning from student to alumni was not always easy. To align students' academic activities with the academic vision of the study program, targeted digital outreach was conducted using videos sent through dominant social media platforms, to improve students' understanding of the program's academic vision. A total of 75 and 46 students participated in the social media survey and understanding test, respectively. The effectiveness of the socialization was evaluated based on student engagement, analysing video performance through social media analytics and measuring improvements in understanding. Results showed a surge in views at specific durations, with students re-watching the video links sent via WhatsApp or Instagram. Additionally, there was a significant improvement in students' understanding of the academic vision, categorized as moderate. Thus, targeted digital outreach-based socialization effectively enhanced students' understanding, though content presentation needed optimization. A collaborative approach was also necessary for broader video distribution.